Heavy metals and radionuclides concentrations in mosses from the region of Northern Greece - Betsou, Ch.; Frontasyeva, M.; Tsakiri, E.; Hansman, J.; Kazakis, N.; Vasilev, A.; Krmar, M.; Ioannidou, A. (HNPS Advances in Nuclear Physics, 2019)
Mosses can be used as biomonitors for investigating the atmospheric deposition of radionuclides and heavy metals. They receive most of their nutrients directly from wet and dry deposition. During the 2015/2016 European moss survey, ninety-five samples of Hypnum cupressiformeHedw. were collected in Northern Greece. They were analyzed to the content of heavy metals using INAA. The concentrations of 137Cs,40K, 7Be and 210Pb radionuclides were determined using gamma spectrometry. Differences have been observed in the activity concentrations between mosses collected from ground surface, rocks, branches and near roots. Finally, a high sampling density was achieved, providing information for the elemental and radionuclides deposition from the atmosphere to terrestrial systems over the region of Northern Greece.